MOTIVATION OF FARMERS IN CULTIVATION OF PLANTS (Pogostemon cablin Benth) IN TIWORO VILLAGE, TIWORO DISTRICT, WEST MUNA DISTRICT - Victor Braganca; Salahuddin Salahuddin; Suriana Suriana; Nurhayu Malik; La Ode Ali Amani (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This studied aimed to determine: (1) the motivation of farmers in cultivating patchouli; and (2) factors that motivate farmers with the motivation of farmers in cultivating patchouli; and (3) the relationship between the factors that motivate farmers and the motivation of farmers in cultivating patchouli in Tiworo Village, Tiworo Islands District, West Muna Regency. This research was conducted in Tiworo Village, Tiworo Islands District, Muna Regency. The research respondents were 32 who were determined by census, namely taking the entire population, namely farmers who cultivate patchouli plants. The analysis in this research is by using Spearman Rank Correlation Analysis. The results showed that: (1) the motivation of farmers in cultivating patchouli was categorized as high; and (2) the factors that were significantly related to the motivation of farmers were capital, the availability of production facilities, the availability of technological facilities, the recommendation of agricultural extension workers and the market, while the factors that were not significantly related to the motivation of farmers in cultivating patchouli plants were the recommendations of friends or neighbors.